The future of Parkinson’s care: a need to expand access - Aslam, Sana; Sharrief, Anjail Z.; Holden, Samantha K.; Fullard, Michelle; Holtrop, Jodi S.; Maw, Anna M.; Amara, Amy W. (Frontiers in Neurology, 2025)
Parkinson’s disease (PD) affects over one million Americans, with prevalence expected to double by 2040, creating rising challenges for healthcare systems. While neurologist-led care, particularly by movement disorder specialists (MDS), is associated with improved patient outcomes, only a small fraction of PD patients access this level of expertise. Many, various, barriers lead to delays or missed opportunities for advanced treatments such as deep brain stimulation and infusion therapies. This Perspective article issues a call to action for improving referral pathways and care coordination in PD, addressing both clinical and systems-level gaps. We propose several pragmatic strategies, including the development of standardized referral criteria supported by clinical decision tools, expanded use of telemedicine and eConsult platforms, and enhanced provider and patient education to promote timely and appropriate access to specialty care. As early diagnostic technologies become more available, the need for structured referral pathways will become even more critical.